Application and prospects of somatic cell reprogramming technology for spinal cord injury treatment - Yang, Riyun; Pan, Jingying; Wang, Yankai; Xia, Panhui; Tai, Mingliang; Jiang, Zhihao; Chen, Gang (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) is a serious neurological trauma that is challenging to treat. After SCI, many neurons in the injured area die due to necrosis or apoptosis, and astrocytes, oligodendrocytes, microglia and other nonneuronal cells become dysfunctional, hindering the repair of the injured spinal cord. Corrective surgery and biological, physical and pharmacological therapies are commonly used treatment modalities for SCI; however, no current therapeutic strategies can achieve complete recovery. Somatic cell reprogramming is a promising technology that has gradually become a feasible therapeutic approach for repairing the injured spinal cord. This revolutionary technology can reprogram fibroblasts, astrocytes, NG2 cells and neural progenitor cells into neurons or oligodendrocytes for spinal cord repair. In this review, we provide an overview of the transcription factors, genes, microRNAs (miRNAs), small molecules and combinations of these factors that can mediate somatic cell reprogramming to repair the injured spinal cord. Although many challenges and questions related to this technique remain, we believe that the beneficial effect of somatic cell reprogramming provides new ideas for achieving functional recovery after SCI and a direction for the development of treatments for SCI.